2010
DOI: 10.1088/2041-8205/723/2/l169
|View full text |Cite
|
Sign up to set email alerts
|

Bright Points in the Quiet Sun as Observed in the Visible and Near-Uv by the Balloon-Borne Observatory Sunrise

Abstract: Bright points (BPs) are manifestations of small magnetic elements in the solar photosphere. Their brightness contrast not only gives insight into the thermal state of the photosphere (and chromosphere) in magnetic elements, but also plays an important role in modulating the solar total and spectral irradiance. Here, we report on simultaneous high-resolution imaging and spectropolarimetric observations of BPs using Sunrise balloon-borne observatory data of the quiet Sun at the disk center. BP contrasts have bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

6
2

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 28 publications
(31 reference statements)
6
55
2
Order By: Relevance
“…The total observing time with image stabilization was more than 33 h, in which SuFI collected nearly 56 000 images in the wavelength range between 210 nm to 400 nm, being above most of the ozone layer in the Earth's atmosphere. In the blue channels at 214 nm, 300 nm, and 312 nm, the solar surface could be observed for the first time at high angular resolution and with unprecedented intensity contrasts Riethmüller et al, 2010;Hirzberger et al, 2010b), thanks to the high optical quality of the instrumentation. IMaX collected high resolution Doppler-and magnetograms with an unprecedented combination of angular resolution and magnetic sensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…The total observing time with image stabilization was more than 33 h, in which SuFI collected nearly 56 000 images in the wavelength range between 210 nm to 400 nm, being above most of the ozone layer in the Earth's atmosphere. In the blue channels at 214 nm, 300 nm, and 312 nm, the solar surface could be observed for the first time at high angular resolution and with unprecedented intensity contrasts Riethmüller et al, 2010;Hirzberger et al, 2010b), thanks to the high optical quality of the instrumentation. IMaX collected high resolution Doppler-and magnetograms with an unprecedented combination of angular resolution and magnetic sensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…A careful analysis of the data (Hirzberger et al, 2010a;Riethmüller et al, 2010;Solanki et al, 2010) reveals that the observed intensity contrasts are remarkably high, showing the extraordinary optical performance of the total system of telescope and instrument, especially the virtual lack of straylight contamination.…”
Section: Discussionmentioning
confidence: 99%
“…2, panel h) find that most of the BPs are only weakly polarized. We use the BP detection method applied by Riethmüller et al (2010) for a direct comparison with their results.…”
Section: Simulations Versus Observations: Bright Pointsmentioning
confidence: 99%
“…Furthermore, the noise levels of the two data sets were comparable. We also calculated the histogram of the circular polarization degree of the set of V5-6 BPs analyzed by Riethmüller et al (2010) (not shown) and compared it with their histogram of the total polarization degree, i.e., Q 2 + U 2 + V 2 integrated over λ in the line, shown in Fig. 2, panel (h) of Riethmüller et al (2010).…”
Section: Circular Polarization Degreementioning
confidence: 99%
See 1 more Smart Citation